2015
DOI: 10.1111/rego.12076
|View full text |Cite
|
Sign up to set email alerts
|

Codes in context: How states, markets, and civil society shape adherence to global labor standards

Abstract: Transnational business regulation is increasingly implemented through private voluntary programs-like certification regimes and codes of conduct-that diffuse global standards. But little is known about the conditions under which companies adhere to these standards. We conduct one of the first large-scale comparative studies to determine which international, domestic, civil society, and market institutions promote supply chain factories' adherence to the global labor standards embodied in codes of conduct impos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
161
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 155 publications
(184 citation statements)
references
References 58 publications
(113 reference statements)
2
161
1
3
Order By: Relevance
“…Research on supply chain labor standards suggests that it is untenable to dismiss the organizational structures adopted in these environments wholesale as myth and ceremony. Studies consistently have shown that, on average, suppliers that adopt various types of legalization and participation structures do, in fact, improve their working conditions over time (Ang et al 2012, Locke et al 2007, 2013, Nadvi et al 2011, Shea et al 2010, Toffel et al 2015. These findings belie a straightforward story of symbolic or cynical adoption.…”
supporting
confidence: 55%
See 2 more Smart Citations
“…Research on supply chain labor standards suggests that it is untenable to dismiss the organizational structures adopted in these environments wholesale as myth and ceremony. Studies consistently have shown that, on average, suppliers that adopt various types of legalization and participation structures do, in fact, improve their working conditions over time (Ang et al 2012, Locke et al 2007, 2013, Nadvi et al 2011, Shea et al 2010, Toffel et al 2015. These findings belie a straightforward story of symbolic or cynical adoption.…”
supporting
confidence: 55%
“…For instance, research has identified regulatory attention and enforcement as important factors that can reduce the decoupling of organizational commitment and practice (Dobbin and Kelly 2007, Marquis and Qian 2014, Short and Toffel 2010. Studies of private organizations' implementation of human rights or corporate social responsibility (CSR) policies have suggested that institutional pressures emanating from activists or the press can likewise increase companies' commitments to better practices (Fransen 2012, Lim and Tsutsui 2012, Marquis et al 2016, Seidman 2007, Toffel et al 2015.…”
Section: Organizational Structures Governing Global Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, theft of intellectual property and patent enforcement is a result of weak patent enforcement in developing country. If we draw from research in business ethics it is established that non-compliance with agreements is especially troublesome in countries with poor public regulatory systems (Locke et al, 2013;Toffel et al, 2014). Fourth, high employee turnover continues to be a problem in several offshore locations.…”
Section: Host Countrymentioning
confidence: 99%
“…Moreover, developed countries could serve as role models for developing countries through market integration, which can result in the harmonisation of institutions and regulatory arrangements (Kucera & Sarna, 2006;Neumayer & de Soysa, 2006). At firm level, Toffel, Short and Ouellet (2015) found better labour rights compliance among suppliers serving buyers located in countries where consumers are wealthy and socially conscious. In addition, Distelhorst and Locke (2017) concluded that importers favour doing business with companies that comply with basic labour and environmental standards.…”
Section: Labour Rights As a Determinant Of Exportsmentioning
confidence: 99%